Study protocol: Developing telephone follow-up scale for patients with disorders of consciousness - Shou, Fangfang; Wang, Jing; Laureys, Steven; Cheng, Lijuan; Huang, Wangshan; Di, Haibo (Frontiers in Public Health, 2023)
Background The significant lack of rehabilitation prognostic data is the main reason that affects the treatment decision-making and ethical issues of patients with disorders of consciousness (DoC). Currently, the clinic's consciousness assessment tools cannot satisfy DoC patients' follow-up needs. Objective The purpose of this study is to construct a sensitive, professional, and simple telephone follow-up scale for DoC patients to follow up on the prognosis, especially the recovery of consciousness, of prolonged DoC patients transferred to community hospitals or at home. Methods This study is to adopt expert consultation to construct and to verify the validity and feasibility of the scale on-site. Conclusion At present, there is a strong demand for portable, accurate, and easily operated scales. It is helpful to improve the rehabilitation data of prolonged DoC patients and provide more basis for their treatment and rehabilitation.